Surviving Life - Svankmajer, Jan; Galvánek, Juraj; Ruzicka, Jan; Helsus, Václav; Issová, Klára; Krónerová, Zuzana (New Wave Films, 2012)
Eugene (Václav Hel us) leads a double life - one real, the other in his dreams. In real life he has a wife called Milada (Zuzana Kronerová); in his dreams he has a young girlfriend called Eugenia (Klára Issová). Sensing that these dreams have some deeper meaning, he goes to see a psychoanalyst, Dr. Holubova, who interprets them for him, with the help of some argumentative psychoanalytical griping from the animated heads of Freud and Jung. As we gradually piecing together Eugene's life story, his dream-world love affair with Eugenia is thwarted by the appearance of other characters, including her little boy Peter, her extortionist ex-husband, and a filthy old woman who keeps warning him not to harm her. Soon after, we discover she is expecting Eugene's child - to the dismay of Dr. Holubova, who believes Eugenia is in fact his anima. And getting your anima pregnant is worse than incest ... [www.amazon.co.uk]
Keywords: DVD-Video